Pengembangan Desa Padang Bindu melalui Optimalisasi Objek Wisata di Kecamatan Semidang Aji - Putra, Raniasa; Budiyanto, M. Nur; Juliantina, Juliantina (Universitas Pahlawan Tuanku Tambusai, 2025)
This community service aims to explore the development potential of Padang Bindu Village through the optimization of tourist attractions in Semidang Aji District, Ogan Komering Ulu Regency, South Sumatra. The main focus of this activity is to identify existing tourism potentials and formulate effective management strategies to enhance tourist appeal and improve the welfare of the local community. The method employed is a qualitative approach with data collection techniques including interviews, observations, and documentation studies. The results indicate that Padang Bindu Village possesses neglected natural tourism potentials, such as waterfalls, lakes, and scenic landscapes, which have not been optimally managed. Moreover, the local community has not been fully involved in the development of the tourism sector. In conclusion, the development of Padang Bindu Village can be achieved through the improvement of tourism support infrastructure, capacity building for local human resources in tourism management, and more intensive promotional efforts. Optimizing existing tourist attractions is expected to increase visitor numbers, promote local potential, and create economic opportunities for the surrounding community.